Dismantling the dualisms for American Pentecostal women in ministry : a feminist-pneumatological approach - Stephenson, Lisa P. (Global Pentecostal and Charismatic Studies, 2012)
The pneumatological magna carta of Acts 2 has never translated into a fully liberating praxis for Pentecostal women in ministry. Scholars have given this problem limited attention, but their works do not adopt the perspective of pneumatology or engage feminist theology. In neglecting pneumatology, Pentecostals have ignored a methodological approach and a dominant orienting motif that is fundamental to their spirituality. In neglecting feminist theology, they proffer an incomplete solution that addresses anthropological paradigms to the exclusion of ecclesiological ones. After analyzing the historical and theological factors resulting in the present situation among American Pentecostal women in ministry, this book proposes a Feminist-Pneumatological anthropology and ecclesiology that address the problematic dualisms that have perpetuated Pentecostal women's ecclesial restrictions.